2022
DOI: 10.3390/su14138025
|View full text |Cite
|
Sign up to set email alerts
|

Demand Response Analysis Framework (DRAF): An Open-Source Multi-Objective Decision Support Tool for Decarbonizing Local Multi-Energy Systems

Abstract: A major barrier to investments in clean and future-proof energy technologies of local multi-energy systems (L-MESs) is the lack of knowledge about their impacts on profitability and carbon footprints due to their complex techno-economic interactions. To reduce this problem, decision support tools should integrate various forms of decarbonization measures. This paper proposes the Demand Response Analysis Framework (DRAF), a new open-source Python decision support tool that integrally optimizes the design and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For other applications with grey-box models, multiple solutions exist. Fleschutz et al [44] propose an energy optimization software framework for industrial applications on a system level, including multiple energy sources, energy storage systems and data-driven load analysis. Within the framework, multiple DR aspects can be optimized, including the peak load.…”
Section: Process Load Modeling and Estimationmentioning
confidence: 99%
“…For other applications with grey-box models, multiple solutions exist. Fleschutz et al [44] propose an energy optimization software framework for industrial applications on a system level, including multiple energy sources, energy storage systems and data-driven load analysis. Within the framework, multiple DR aspects can be optimized, including the peak load.…”
Section: Process Load Modeling and Estimationmentioning
confidence: 99%
“…The high share of integrated RES contributes more economical benefits, reduces greenhouse emissions from the environment, and provides better energy security. To analyze the economic and environmental benefits, a DR program was conducted on the residential MG system [27][28][29][30][31], CHP-based reconfigurable MG system [32], demand response analysis framework with multiple BSS [33], and CHP-based MG with multiple markets [34]. The cost of the MG emitted emission and the demand cost are optimized simultaneously by linear programming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new demand response analytical framework (DRAF) was analyzed in a python environment for (i) DR in the production process, (ii) design optimization of battery with a PV system, and (iii) DR of distributed thermal energy resources. It was observed that using Pareto front through Price based DR, cost and emissions are reduced [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To quantify the value of flexibility for this company, we formulate a deterministic MILP using technology components of version v0.3.0 [40] of the open-source Python Demand Response Analysis Framework (DRAF), a modular tool for economic and environmental evaluation of DR [41]. An overview of the model is shown in Fig.…”
Section: Overviewmentioning
confidence: 99%
“…DRAF and most used technology components are detailed in [41]. However, model parts that are crucial (cost and carbon balances, HP, BEV) or not described in [41] such as wind turbine (WT), pressurized H 2 storage (H 2 S), proton exchange membrane fuel cell (FC), proton exchange membrane electrolyzer (Elc), and direct air capture (DAC) are described in this section. We model one year with 8,760 hourly time steps t ∈ T , so ∆t = 1 h. We assume perfect foresight.…”
Section: Overviewmentioning
confidence: 99%